Structure and geology of the continental shelf of the Laptev Sea, Eastern Russian Arctic - Drachev, Sergei S; Savostin, Leonid A; Groshev, Victor G; Bruni, Inna E (Tectonophysics, 1998)
The Laptev Sea is of great significance for studying the processes of the initial breakup of continents. It is the southern termination of the Gakkel spreading ridge and thus the location of structural features resulting from a continental margin/spreading ridge intersection. The present-day understanding of the Laptev Shelf geology is based on the Russian multichannel seismic reflection data and extrapolation of the terrestrial geology. Geologic and plate-kinematic data are used to constrain the interpretation of the seismic reflection data. The Laptev Rift System consists of several deep subsided rifts and high standing blocks of the basement. From west to east these are: the West Laptev and South Laptev rift basins, Ust' Lena Rift, East Laptev and Stolbovoi horsts, Bel'kov-Svyatoi Nos and Anisin rifts. The central and eastern parts of the shelf have the greatest contrasts in the gravity field ranging from −60 mGal over the rifts to 50 mGal over the horsts. The rifts contain up to five seismic stratigraphic units bounded by clear regional reflectors and underlain by folded heterogeneous basement. They are suggested to be Late Cretaceous to Holocene in age and reflect different stages of spreading ridge/continental margin interaction. The estimated total thickness of the rift-related sediments varies between 4 and 8–10 km while the sedimentary cover on the uplifts is significantly reduced and generally does not exceed 1–2 km. An eastward decrease of the total thickness of the sedimentary sections from about 10 km in the South Laptev Basin to 4–5 km in the Bel'kov-Svyatoi Nos Rift and the simplicity of the entire rift structure may indicate a rejuvenation of the rifts in the same direction. The entire rift system is covered by the uppermost seismic unit, which probably reflects a deceleration of the rifting during the last reorganization of the North American/Eurasian plate interaction since about 2 Ma.